Evaluating the safety and efficacy of felbamate in the context of a black box warning: A single center experience - Shah, Yash D.; Singh, Kanwaljit; Friedman, Daniel; Devinsky, Orrin; Kothare, Sanjeev V. (Epilepsy & behavior, 2016)
Felbamate was approved in 1993 to treat partial seizures with and without secondary generalization in adults and in Lennox–Gastaut Syndrome in children. Its use was later restricted when rare but fatal cases of aplastic anemia and hepatic failure were identified. This single center analysis retrospectively evaluated the safety and efficacy of felbamate in a cohort of children, adolescents, and adults with epilepsy. A chart review identified 103 patients taking felbamate. The range of felbamate dose was 300–4500mg (mean: 1800±900mg). The duration of therapy ranged from 1month to 20years (mean duration: 35±45months). Eighteen (17.5%) subjects experienced adverse events including insomnia, nausea, vomiting, decreased appetite, weight loss, gastric discomfort, diarrhea, mood and behavioral problems, high blood pressure, headache, and elevated liver enzymes. Out of these, 6 (5.9%) patients discontinued the therapy. No hepatic failure or agranulocytosis was observed. Fifty-nine (57.72%) patients achieved ≥50% reduction in seizure frequency, and 30 (29.12%) patients achieved seizure freedom. These findings suggest that felbamate is safe, well tolerated, and effective in treatment of various types of epilepsy syndromes. •Felbamate (FBM) is used to treat partial seizures and Lennox–Gastaut syndrome.•Black box warning was added because of fatal cases of aplastic anemia and liver failure.•We retrospectively analyzed FBM's safety and efficacy in 103 patients with epilepsy.•FBM was reasonably safe and effective to treat epilepsy.